Planificación tributaria de la compañía de seguridad Sociosecurity Cía. Ltda. De la ciudad de Babahoyo en los periodos 2020-2021. - Inga Mayorga, Yandri Javier (2022)
The Security company SOCIOSECURITY CIA LTDA is located in the City of Babahoyo of the Province of the RIOS in the streets Martin Icaza and Second Pedestrian, is dedicated to the provision of services of security guards, all kinds of activities related to private investigators without distinction of clients or object of the service is also dedicated to other types of security services such as private investigation such as fingerprint detectors and detectors of lies among others, etc. The central problem of the company is that it does not carry out an adequate control of its tax accounting process, which leads to the company not having an optimal tax planning that allows it to reduce its tax burden in the field of income tax. The objective of this study is to identify the tax benefits not applied by the company in the presentation of its tax obligations and can make use of the tax deductions allowed by the Internal Tax Regime Law, Regulations for the application of the Internal Tax Regime Law and current resolutions. The study is structured under the Research sublinium "Financial, Tax Management and Social Commitment" lines that are framed and established in the School of Accounting, Auditing and Finance.